Evaluasi Sistem Pengendalian Internal Persediaan Bahan Baku Baku Untuk Meningkatkan Efektivitas Penggunaan Bahan Baku (Studi Kasus pada Departemen Production Planning and Inventory Control PT. Chitose Internasional Tbk-Cimahi) - Salma Shinta Anggraini; Sudjana Sudjana (Indonesian Accounting Literacy Journal, 2020)
Raw material inventory is one of the company's assets that has an important position in a company, both in the trading companies and industrial companies (manufacturing companies). Inventory influences the company's production process which will produce goods to be sold to gain the company's profit. Therefore, the company must manage its inventory well for the smooth production process and the company also needs effective internal control of raw materials inventory in order to assist management in the company in controlling operational activities that has complex scope so that the activity is effective and efficient. Chitose International Inc, has implement internal control of raw material inventory, but in practice there are often problems that occur. Therefore, an evaluation must be implemented on the internal control system of raw material inventory. The research method used is a qualitative descriptive method supported by data analysis tools such as control matrix. Data collection techniques are collected by observation, interviews, documentation, and questionnaires that distributed to the staff of the Department of Production Planning and Inventory ControI, Accounting Department, and Internal Auditors at Chitose International Inc.